2002
DOI: 10.2190/avm3-8gu8-jw70-5rx5
|View full text |Cite
|
Sign up to set email alerts
|

A Primary Care Perspective on Prevailing Assumptions about Persistent Medically Unexplained Physical Symptoms

Abstract: In this sample of primary care patients with persistent unexplained physical symptoms, we found little evidence of discrete somatic syndromes. The level of health care use is no indication of mental state or level of disability, and the findings are equally consistent with depression or anxiety being secondary to disability and its consequences as with them being primary. The observed collaboration between patients and their doctors carries the risk of shaping, reinforcing, and legitimizing dubious syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…Mean age was 46 years (range 16-85). They had consulted GPs a mean of 6.1 times in the previous 6 months (range 0-39) and reported a mean of 2.3 symptoms (range [1][2][3][4][5][6][7][8] in the recorded consultation. These characteristics did not differ between those providing complete and incomplete data on the Patient Requests Form.…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean age was 46 years (range 16-85). They had consulted GPs a mean of 6.1 times in the previous 6 months (range 0-39) and reported a mean of 2.3 symptoms (range [1][2][3][4][5][6][7][8] in the recorded consultation. These characteristics did not differ between those providing complete and incomplete data on the Patient Requests Form.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…Patients with medically unexplained symptoms (MUS) have as poor a quality of life as those with comparable symptoms caused by disease 6,7 . Many doctors find these patients challenging [8][9][10][11][12] and provide disproportionate levels of health care, which is often ineffective and might sometimes increase patients' dependence 7,[13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that multiple somatic symptoms are related to the depression and tension symptoms [34,37]. It is apparent that the results regarding reported depression and tension symptoms could possibly indicate a psychiatric disorder, as has been reported earlier [12,23,37,39].…”
Section: Discussionmentioning
confidence: 60%
“…Multiple or unexplained symptoms may signify a potentially treatable mood or anxiety disorder [12]. In a sample of primary care patients with persistent unexplained physical symptoms, Stanley et al [23] found little evidence of discrete somatic syndromes. However, van der Wall et al [24] reported that musculoskeletal complaints are common among the adult general population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation